Identification of dominant lactic acid bacteria and yeast in rice sourdough produced in New Zealand - Yang Q; Rutherfurd-Markwick K; Mutukumira AN (Elsevier BV, 2021)
This study characterised a commercial New Zealand gluten free (GF) rice sourdough and its starter culture composition. Acidity of the mother sourdough, dough before proofing and dough after proofing was determined during the production of rice sourdough bread, and colour was measured for the baked bread. Yeast and lactic acid bacteria (LAB) were enumerated in the rice sourdough samples and representative colonies characterised using API kits and sequenced by the Internal Transcribed Spacer and 16 S rRNA region. Sourdough LAB isolates were identified as Lactobacillus (L.) papraplantarum DSM 10667 and L. fermentarum CIP 102980 and the yeast isolates as Saccharomyces (S.) cerevisiae CBS 1171. Dough acidity increased significantly (p < 0.05) during fermentation due to the metabolic activities of the sourdough cultures. After baking, the colour of the rice sourdough bread crust was similar to that of unleavened wheat bread (golden brown). The improved colour of the rice sourdough bread crust may be a result of combined use of sourdough technique and optimal baking conditions. The results of this study may allow bakers to improve the overall quality of GF rice sourdough baked bread by selecting suitable fermentation and baking parameters.
Keywords: Gluten-free sourdough; Lactobacillus plantarum; Rice sourdough starter culture; Saccharomyces cerevisiae